A comparative aroma profiling, antioxidant activity, and total phenolic content analysis of three Philippine bignay (Antidesma bunius) cultivars - Amador, Arleen Joy Vidallon (Animo Repository, 2022)
The Antidesma bunius, more commonly known as bignay, is an indigenous fruit in the Philippines that is consumed raw and can also be processed into food products, including wine. The processing of bignay is gaining momentum in the Philippine small to medium-scale market. In the country, this fruit is cultivated by farmers, and some are identified as Common, Kalabaw, and Pugo. These cultivars differ in appearance and taste, but not enough studies were conducted to specifically identify the difference in their chemical composition. In this study, the volatile secondary metabolites, which are relevant in the flavors of fruits and food industries applications, were determined and compared among the three cultivated varieties. The samples were subjected to Headspace Gas Chromatography/Mass Spectrometry (HS-GC/MS) to identify and/or quantify the volatile organic compounds (VOCs) present. To further evaluate and compare the cultivars, in vitro antioxidant analysis using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and Total Phenolic Content (TPC) were done with the bignay’s methanolic extracts. A total of 8 compounds were putatively identified in the HS-GC/MS analysis, with the Pugo cultivar (PC) showing a unique aroma profile. Both the DPPH assay and TPC test showed that PC has excellent antioxidant activity and capacity compared to the other cultivars.